Scope of Practice of Forensic Midwifery: An Integrative Review - Ziba Taghizadeh; Khadijeh Azimi; Masoud Ghadipasha; Asieh Jafari; Maryam Pourbakhtiar (Mashhad University of Medical Sciences, 2020)
Background & aim: Forensic midwifery is a new major which has been established in response to the need of endangered women for forensic services and also the lack of service provision in this domain. However, there are ambiguities in the definition of this major and its scope of practice. The present study was conducted to investigate the scope of practice in forensic midwifery. Methods: In this integrative review, the articles related to the subject of interest were searched in several database including PubMed, Scopus, CINHAL and Google Scholar. All kinds of publications including reviews and standards, qualitative, quantitative, or mixed methods studies were included in the review regardless of the publication date. The data related to the scope of practice in forensic midwifery were extracted using a wide and in-depth analysis, in addition to using an expert panel for validation. To do the analysis, every concept representing scope of practice was coded and similar codes were classified into themes. Results: The search process resulted in retrieval of 43 articles. Based on the reviewed papers, the scope of practice in forensic midwifery divided into four categories including the practices related to reproductive issues, violence, malpractice in obstetrics and gynecology profession, and the improvement of the professionalism in midwifery domain. Conclusion: Considering the potentials of forensic midwifery, the graduates of this major could have an important role in the protection of women's rights in forensic situations.